The Effect of Service Quality, Physical Work Environment and Organizational Culture on Employee Performance at the Education Office of Mentawai Islands District - Sitama Waruwu; Khairul Khairul; Hurip Pratomo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of service quality, physical work environment and organizational culture on employee performance at the Mentawai Islands District employee performance is not yet high at the Department of Education and Culture of the Mentawai Islands District. This type of research uses a quantitative approach with multiple linear regression method. Data collection techniques with questionnaires. The respondents of this study were 59 employees of the Department of Education and Culture of the Mentawai Islands District. The sampling method used the total sampling method where the entire population in this study was used as the research sample. Hypothesis testing was calculated using the IBM Statistical Package for Social Science (SPSS) version 24.0 program. From the results of this study, it was found that partially service quality had no significant effect on employee performance, physical work environment had a significant effect on employee performance, organizational culture had a significant effect on employee performance and service quality, physical work environment and organizational culture simultaneously had a significant effect on employee performance at Department of Education and Culture of the Mentawai Islands District.